Feasibility of accelerated simultaneous multislice diffusion‐weighted MRI of the prostate. Issue 5 (15th February 2017) - Weiss, Jakob; Martirosian, Petros; Taron, Jana; Othman, Ahmed E.; Kuestner, Thomas; Erb, Michael; Bedke, Jens; Bamberg, Fabian; Nikolaou, Konstantin; Notohamiprodjo, Mike
Abstract : Purpose: To assess the feasibility of simultaneous multislice (SMS) single‐shot echo‐planar‐imaging (EPI) for accelerated diffusion‐weighted imaging (DWI) of the prostate. Materials and Methods: For phantom measurements a dedicated DWI phantom with different sucrose concentrations was used. In addition, 10 volunteers and 16 patients with suspected prostate cancer were examined for in vivo measurements. All examinations were performed with a 3T magnetic resonance imaging (MRI) system. A prototype simultaneous multislice EPI sequence (DW‐EPISMS ; acquisition time 3:14 min) was acquired and compared to a single‐shot EPI sequence (DW‐EPISS ; acquisition time 6:12 min) serving as a standard of reference. Different image quality parameters of EPISMS were assessed qualitatively (overall image quality, anatomic differentiability, lesion conspicuity, image noise, distortion; two independent readers; 5‐point Likert‐scale [5 = excellent]) and quantitatively (ADC‐values by calculating interclass correlation [ICC] and Bland–Altman limits of agreement [LoA] as measures for reproducibility) and compared to DW‐EPISS . Results: DW‐EPISMS allowed for a substantially reduced acquisition time as compared to DW‐EPISS (˜50%). Bland–Altman plots revealed robust measurement repeatability for DW‐EPISMS in the phantom study. Overall image quality did not significantly differ between DW‐EPISMS and DW‐EPISS (b1500 images P  = 0.5; ADC maps P  = 0.7). Only in b1500 DW images was subjective image noise rated significantly higher in DW‐EPISS than in DW‐EPISMS ( P  = 0.006). Quantitative analysis of ADC‐values revealed not significant differences between DW‐EPISMS and DW‐EPISS ( P  = 0.7) and high measures for reproducibility ICC ≥0.96. Conclusion: Simultaneous multislice DWI is feasible for accelerated prostate MRI allowing for a substantially reduced examination time with similar image quality and ADC‐values as compared to a standard of reference DWI sequence. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1507–1515.